Screening for antifungal-producing bacteria from Piper nigrum plant against Phytophthora capsici - Toh, S. C.; Samuel, Laly; Awang, A. S A H (Universiti Putra Malaysia, 2016)
Piper nigrum, commonly known as black pepper, is one of the most important spice crops with high demand by the world market. However, diseases like foot rot and stem blight cause by Phytophthora capsici have become the important production constraints in black pepper industry. The frequent application of toxic fungicides to counter the diseases in pepper plantations has raised certain environmental issues. In order to mitigate the use of fungicides, biological approach to control P. capsici has been suggested. In this study, endophytic bacteria were isolated from six P. nigrum roots and screened for in vitro antagonistic activity against P. capsici through dual culture, mycelial growth, spore germination and double plate assay. The antagonism testing involved the secretion of volatile and diffusible bioactive compounds by the endophytic bacteria. Out of 19 isolates tested, two isolates DB(2)7 and SB(2)6 produced volatile bioactive compounds and these two isolates showed highest antagonism against P. capsici mycelia with the percentage of inhibition up to 47.63% and 43.33%, respectively. Diffusible compounds from isolates DB(2)7, DB(2)9 and SB(2)6 produced clear zones in spore germination test with radii measurements of 10.0-17.0 mm. Three isolates with promising antifungal activity were further characterised through 16S rDNA sequencing. The analysis of their sequences via National Center for Biotechnology Information (NCBI) suggests close identity towards Enterobacter cancerogenus, Enterobacter cloacae and Enterobacter asburiae. This research study demonstrated that these endophytic bacteria isolates are potentially to be used as biocontrol agent in pepper cultivation